The possibilities to benefit from hasmer and hasak sheep types with akkaraman sheep in breeders' flocks for slaughter lamb production - Ahmet Hamdi Aktaş; Mehmet Çolak; Mehmet Emin Tekin; Necdet Akay; Tülay Canatan Yılmaz; Şükrü Dursun (Eurasian Journal of Veterinary Sciences)
Aim: This trial was conducted to research the possibilities to benefit from Hasmer and Hasak sheep types with Akkaraman sheep in breeders' flocks for slaughter lamb production. In the study the growth characteristics, survival ability and fattening performances of Hasak x Akkaraman F1 and Hasmer x Akkaraman F1 crossbred and pure Akkaraman lambs were investigated. Materials and Methods: In the trial, the growth characteristic and survival ability of 87 head purebred Akkaraman, 73 head Hasmer x Akkaraman F1 and 104 head Hasak x Akkaraman F1 crossbred lambs were investigated. For investigation of fattening performance, 10 head Hasak x Akkaraman F1, 10 head Hasmer x Akkaraman F1 and 10 head pure Akkaraman male lambs at an average of 75 dayold and with a range of 19-24 kg live weights were fed intensively as groups for 70 days. Results: Differences in live weight and average daily weight gain of male lambs at day 150 and various periods were significant (P<0.022) while the differences of female lambs were insignificant (P>0.126). Hasmer x Akkaraman F1 crossbred lambs grew slower than the other two genotypes when they were fed on pasture. The differences between the genotypes for survival rates until weaning were insignificant. Hasmer x Akkaraman F1 crossbred lambs had higher (P<0.004) live weight and average daily weight gain than the other two group lambs in the intensive fattening. Conclusion: It is concluded that both Hasmer and Hasak sheep types can be used as sire lines for slaughter lamb production in Akkaraman sheep.